Intoxicating Zion: a social history of hashish in Mandatory Palestine and Israel - Ram, Ḥagai (Stanford University Press, 2020)
The drug trade in the Levant -- Smuggling in Mandatory Palestine -- The underworld of users -- Jews and interwar Oriental fantasies -- Hashish trafficking in Israel -- Mizrahim and the "perils" of hashish smoking.